2013
DOI: 10.1590/s0100-67622013000400008
|View full text |Cite
|
Sign up to set email alerts
|

Quantificação de biomassa e estocagem de carbono em uma floresta estacional semidecidual, no Parque Tecnológico de Viçosa, MG

Abstract: RESUMO -Os objetivos deste trabalho foram quantificar a biomassa e a estocagem de carbono em uma Floresta Estacional Semidecidual,com área de 44,11 ha, localizado no Parque Tecnológico de Viçosa, MG e avaliar as diferenças entre as metodologias de quantificação de biomassa propostas pelo Painel Intergovernamental sobre Mudanças do Clima (IPCC) e utilizando equações regionais. Para a quantificação da biomassa e estocagem de carbono da área utilizou-se duas metodologias distintas, uma com equações regionais e ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 9 publications
1
18
1
9
Order By: Relevance
“…Inventory of Organic Carbon... Floresta e Ambiente 2019; 26(4): e20160426 that indicated by the Intergovernmental Panel on Climate Change (Eggleston et al, 2006), which suggests 37% for the litter. Torres et al (2013) observed an average of 52% of C content in the litter in a Semi-Deciduous Seasonal Forest in Minas Gerais. On the other hand, Higuchi & Carvalho (1994), in a Tropical Forest in the Amazon Region, and Morais et al (2017), in the Cerrado vegetation of the state of Minas Gerais, found mean C contents in the litter of 39% and 44%, respectively.…”
Section: Organic Carbon In Littermentioning
confidence: 92%
“…Inventory of Organic Carbon... Floresta e Ambiente 2019; 26(4): e20160426 that indicated by the Intergovernmental Panel on Climate Change (Eggleston et al, 2006), which suggests 37% for the litter. Torres et al (2013) observed an average of 52% of C content in the litter in a Semi-Deciduous Seasonal Forest in Minas Gerais. On the other hand, Higuchi & Carvalho (1994), in a Tropical Forest in the Amazon Region, and Morais et al (2017), in the Cerrado vegetation of the state of Minas Gerais, found mean C contents in the litter of 39% and 44%, respectively.…”
Section: Organic Carbon In Littermentioning
confidence: 92%
“…A fração de maior acúmulo de biomassa viva na árvore é encontrada acima do solo (TORRES et al, 2013). A maior disponibilidade de água, luz e nutrientes favorece o desenvolvimento das plantas (CHASE et al, 2016), e consequentemente maior acúmulo de AGB.…”
Section: )unclassified
“…Various disturbances have occurred over the years in the forest fragment, including the extraction of wood and planting of agricultural cultivars and of eucalypt (Torres et al, 2013). Regeneration of the native vegetation in the area has been underway however, for approximately 25 years.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…For this, three trees from each species were selected as well as by diameter class for the partial analysis of the trunk, which corresponds to the removal of a wood sample at a height of 1.30 m, with the help of increment borers (Torres et al, 2017). The material was then taken to the laboratory where part of it was used to determine the basic wood density for each species, according to the methodology described by Vital (1984) andNBR 11941 (ABNT, 2003), and the other part submitted to complete calcination in an muffle furnace to determine the carbon content, according to the methodology described by Torres et al (2013).…”
Section: Data Collection and Analysismentioning
confidence: 99%